Bryostatin‐1 ameliorated experimental colitis in Il‐10−/− Mice by protecting the intestinal barrier and limiting immune dysfunction. Issue 8 (28th June 2019) - Zuo, Lugen; Li, Jing; Ge, Sitang; Ge, Yuanyuan; Shen, Mengdi; Wang, Yan; Zhou, Changmin; Wu, Rong; Hu, Jianguo
Abstract: Bryostatin‐1 (Bry‐1) has been proven to be effective and safe in clinical trials of a variety of immune‐related diseases. However, little is known about its effect on Crohn's disease (CD). We aimed to investigate the impact of Bry‐1 on CD‐like colitis and determine the mechanism underlying this effect. In the present study, 15‐week‐old male Il‐10 −/− mice with spontaneous colitis were divided into positive control and Bry‐1‐treated (Bry‐1, 30 μg/kg every other day, injected intraperitoneally for 4 weeks) groups. Age‐matched, male wild‐type (WT) mice were used as a negative control. The effects of Bry‐1 on colitis, intestinal barrier function and T cell responses as well as the potential regulatory mechanisms were evaluated. We found that the systemic delivery of Bry‐1 significantly ameliorated colitis in Il‐10 −/− mice, as demonstrated by decreases in the disease activity index (DAI), inflammatory score and proinflammatory mediator levels. The protective effects of Bry‐1 on CD‐like colitis included the maintenance of intestinal barrier integrity and the helper T cell (Th)/regulatory T cell (Treg) balance. These effects of Bry‐1 may act in part through nuclear factor erythroid 2‐related factor 2 (Nrf2) signalling activation and STAT3/4 signalling inhibition. The protective effect of Bry‐1 on CD‐like colitis suggests Bry‐1 has therapeutic potential in human CD, particularly given the established clinical safety of Bry‐1.